Determinants Influencing Awareness and Healthy Practices among a Sample of Insulin-dependent Diabetic Egyptian Patients: A Rural Community-based Study - Metwally, Ammal M.; Yousof, Hanaa; Elkholy, Monira M.; Eletreby, Lobna A.; Barakat, Abeer A.; Abd El Dayem, Soha M.; Abdelrahman, Mohamed; Eldeeb, Sherif M. (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: The prevalence of diabetes mellitus (DM) is predicted to increase over the coming years. AIM: The objectives of the study were to measure the level of awareness and healthy practices related to five healthy domains and assess the effect of different demographic characteristics, glycated hemoglobin (HbA1c) level, and body mass index (BMI) on these levels among diabetic patients in a rural Egyptian village. METHODS: A cross-sectional study was done on 300 selected insulin-dependent diabetic patients resident in an Egyptian village. Data were collected using a questionnaire covering five domains: General disease awareness and management compliance practice, check-up, foot care, diet, and physical activity. HbA1c and BMI were also measured as an impact of the management adherence. RESULTS: The study found that more than three quarters of the participants (82.0%) were uncontrolled or poorly uncontrolled (HbA1c >8) diabetics and 76.0% were either obese or morbidly obese. Total awareness and practices percentage scores were low (42.4 ± 16.8% and 40.5 ± 12.3%, respectively). The linear regression model showed that high educational level had significantly positive effects on both the total awareness and practice scores as well as their domains. The study found that female participants and those having relatives with DM had significantly higher diet awareness and practice scores (p < 0.05). Younger age had significantly higher scores on foot care and diet awareness scores, physical activity, general disease awareness, and management compliance practices domains. CONCLUSION: The studied awareness and practice domains were inadequate. Their improvement is cornerstones to impact glycemic control of diabetics and control their health risks, especially in rural communities.